Paneth cell development in the neonatal gut: pathway regulation, development, and relevance to necrotizing enterocolitis - Yang, Jiahui; Shi, Yongyan (Frontiers in Cell and Developmental Biology, 2023)
Necrotizing enterocolitis (NEC) is an enteric acquired disease with high mortality that usually occurs in premature infants and neonates. Paneth cells are intestinal epithelial cells (IECs) that contain eosinophilic granules and are located in Lieberkühn crypts. An increasing number of animal and human experiments have demonstrated that Paneth cells are involved in the progression of NEC; however, the underlying mechanisms remain unclear. In this review, we summarize the features of Paneth cells, including their immune function, association with gut microbiota and intestinal stem cells, and mechanism of regulation of IEC death. In addition, we explore the possible mechanisms by which Paneth cells affect NEC and provide a new scope for the diagnosis and treatment of NEC.